(untitled) (Journal of Hama University, 2024)
The research stopped on binary of the self and the theme through a group of binaries: The self and the beloved, the self and the people, the self and the reality, the self and the other self, the self and the wounds, the self and the worries, the self and the friends, the self and the national issues that confirmed that the relationship between the self and the theme in the romantic text is a confrontational relationship.The romantic literature was not an image of society, but rather, an image of what society wants to be, and the theme was not the focus of the self’s concern as much as the self’s pain and turmoil. Due to the exaggeration of the romantic self and its uniqueness, the self prevailed over the theme, therefore the romantic text recorded the impact of the theme on the poets sentiment regardless of the subject matter